2017
DOI: 10.1111/mmi.13859
|View full text |Cite
|
Sign up to set email alerts
|

The APSES protein Sok2 is a positive regulator of sporulation in Ashbya gossypii

Abstract: Ashbya gossypii is a homothallic, flavinogenic, filamentous ascomycete that starts overproduction of riboflavin and fragments its mycelium quantitatively into spore producing sporangia at the end of a growth phase. Mating is not required for sporulation and the standard homothallic laboratory strain is a MATa strain. Here we show that ectopic expression of Saccharomyces cerevisiae MATα2 in A. gossypii completely suppresses sporulation, inhibits riboflavin overproduction and downregulates among others AgSOK2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Regarding the riboflavin production in A. gossypii, one missense homozygous mutation (1180G → A) was detected in AgSOK2 gene (AGOS_ABR055C) of MT strain. AgSOK2 is one of fungal-specific group of transcription factors and involved in the sporulation and riboflavin production in A. gossypii [34]. Deletion of AgSOK2 gene led to the strong reduction of the riboflavin production and the deficiency of the sporulation by the downregulation of AgIME2 and AgNDT80 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the riboflavin production in A. gossypii, one missense homozygous mutation (1180G → A) was detected in AgSOK2 gene (AGOS_ABR055C) of MT strain. AgSOK2 is one of fungal-specific group of transcription factors and involved in the sporulation and riboflavin production in A. gossypii [34]. Deletion of AgSOK2 gene led to the strong reduction of the riboflavin production and the deficiency of the sporulation by the downregulation of AgIME2 and AgNDT80 gene.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that in O . polymorpha PKA regulates EFG1 to signal nitrogen depletion, because PKA is known to regulate Efg1 orthologs in Eremothecium (Ashbya) gossypii [ 59 ] and S . cerevisiae [ 28 , 57 ], as well as C .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that a fungal specific transcription factor, encoded by the APSES protein Sok2, is downregulated in an α2 overexpressing strain. SOK2 deletion completely blocks sporulation (although not sporangium formation), e.g., via downregulation of IME2 [58]. Thus, the effect of α2 overexpression may be indirect.…”
Section: The Gear-box Of Sporulationmentioning
confidence: 99%